Risk of periodontal disease in patients with asthma: A nationwide population-based retrospective cohort study - Te Chun Shen (2018)
Background: Studies have reported an association between asthma and oral diseases, including periodontal diseases. The aim of this retrospective study is to investigate risk of periodontal diseases for patients with asthma. Methods: Using the claims data of National Health Insurance of Taiwan and patients without a history of periodontal diseases, 19,206 asthmatic patients, who were newly diagnosed from 2000 through 2010, were identified. For each case, four comparison individuals without history of asthma and periodontal disease were randomly selected from the general population and frequency matched (categorical matched) by sex, age, and year of diagnosis (n = 76,824). Both cohorts were followed to the end of 2011 to monitor occurrence of periodontal diseases. Adjusted hazard ratios (aHRs) of periodontal disease were estimated using Cox proportional hazards regression analysis. Results: Overall incidence of periodontal diseases was 1.18-fold greater in the asthma cohort than in the comparison cohort (P <0.001). Patients with at least three emergency visits annually had an aHR of 55.9 (95% confidence interval [CI] = 50.6 to 61.7) for periodontal diseases compared with those with a mean of less than one visit. Patients with at least three admissions annually also had a similar aHR (51.8) for periodontal disease. In addition, asthmatic patients on inhaled corticosteroid (ICS) therapy had greater aHRs than non-users (aHR = 1.12; 95% CI = 1.03 to 1.23). Conclusions: In the studied population, asthmatic patients are at an elevated risk of developing periodontal diseases. The risk is much greater for those with emergency medical demands or hospital admissions and those on ICS treatment.